Epidemiology of Taenia saginata taeniosis/cysticercosis: A systematic review of the distribution in the Middle East and North Africa - Saratsis, A.; Sotiraki, S.; Braae, U.C.; Devleesschauwer, Brecht; Dermauw, Veronique; Eichenberger, R.M.; Thomas, Lian F.; Bobić, B.; Dorny, P.; Gabriël, S.; Robertson, L.J. (Springer, 2019)
Background The zoonotic parasite Taenia saginata utilizes bovines as an intermediate host (causing cysticercosis) and humans as the definitive host (causing taeniosis). The public health burden of T. saginata is assumed to be low, but the economic burden is large, due to the resources utilized in the detection and condemnation of infected carcasses and carcass parts. As part of a collaborative effort to synthesize worldwide epidemiological data on this parasite, we present here the results of a systematic review on the distribution of T. saginata taeniosis and bovine cysticercosis in the Middle East and North Africa (MENA). Methods Information on the occurrence and prevalence of T. saginata taeniosis and cysticercosis in the MENA region was obtained through a systematic review of published and grey literature, including OIE reports, published between January 1st, 1990 and December 31st, 2017. Results A total of 63 publications were retrieved across the 21 MENA countries. Taenia saginata taeniosis was reported in 11 of these countries, whereas unspecified taeniosis was reported for a further seven. Microscopy-based prevalence values ranged between 0.02–8.6%. Bovine cysticercosis prevalence estimates based on meat inspection were only reported for Egypt and Israel, with prevalence data ranging between 0.2–20% and 0.1–9.1% for cattle and buffaloes, respectively. The presence of bovine cysticercosis could be confirmed for 10 additional countries through OIE reports. Conclusions Human taeniosis occurrence was confirmed for 86% (18/21) of the countries in the MENA region, although in several of these countries the species responsible was not specified. Religious prohibitions on the consumption of pork and the limited extent of pig farming across much of this region, however, suggest that many reported taeniosis cases are likely to be attributable to T. saginata rather than Taenia solium or Taenia asiatica. There was a paucity of data regarding both the prevalence and economic impact of bovine cysticercosis. More detailed epidemiological data on both T. saginata taeniosis and bovine cysticercosis could be obtained by adopting an integrated “One Health” approach, considering the characteristics (e.g. ecosystem related and sociopolitical aspects) of the MENA region. Compared with more conventional approaches, this could lead to an enhanced performance and cost-effectiveness of surveillance systems.